The Effect of Local Governance on Firm Productivity and Resource Allocation : Evidence from Vietnam - Tan, Shawn W.; Tran, Trang T. (World Bank, Washington, DC, 2017)
Governance quality plays a key role in private sector development: competent bureaucrats not only create good policies and regulations but also effectively implement them to shape the business environment. The authors exploit Vietnam’s decentralization of administrative tasks since the early 2000s to test this hypothesis. The authors examine how changes in the provincial administration of national business regulations affect firms through two channels: within firm productivity levels and resource allocation across firms. Their results show that better overall business environment has a positive impact on firm productivity, and this effect is driven by a reduction in corruption levels, the risks of land expropriation, and entry regulations. The authors also find that high productivity firms are generally more able to take advantage of the improvements in business environment. However, better implementation of entry regulations matters most for less productive firms. The authors do not find evidence for the impact of business environment quality on province-level market efficiency.